toothbrush 95g toiletries 1.4kg shoes 3 1/8 kg beach towel 0.6kg clothes 8580g what's the total weight

Answers

Answer 1
Answer: toothbrush = 95g
toiletries = 1.4kg
shoes = 3 1/8 kg
beach towel = 0.6 kg
clothes = 8580 g

2 units are present, grams and kilograms, we need to convert one of these units into the other.

since majority of the items are in kg, we convert the g to kg.

1 kg = 1000 g

toothbrush: 95g * 1kg/1000g = 95kg/1000 = 0.095 kg
clothes: 8580g * 1kg/1000g = 8580kg/1000 = 8.58 kg
shoes 3 1/8 kg = 3.125kg
 
toothbrush:        0.095 kg
toiletries             1.400 kg
shoes                 3.125 kg
beach towel       0.600 kg
clothes               8.580 kg
total weight      13.800 kg

   
Answer 2
Answer:

Answer:

Step-by-step explanation:

Hi sorry for bathed the you do you no the answer please


Related Questions

What s the answer? 16x-12x=2
An elevator is going 180 feet above the first floor each second the 12 feet it descent 12 feet
Label each function as even, odd, or neither.
The sum of three numbers is 2100. The first number (x) is equal to the sum of the other two (y and z) which are equal to each other. What are the three numbers (x, y, and z)? A) (1050, 525, 525) B) (1050, 524, 525) C) (1050, 526, 523) D) (1051, 525, 524)
Doris put $4000 in a 2 year cd paying 6% interest, compounding monthly. after 2 years, she withdrew all her money. what was the amount of the withdraw?

Simplify by factoring. Assume that no radicands were formed by raising negative numbers to even powers. two questions below that i need help on√(148)

\sqrt[4]{80}

Answers

√(148)=√(4\cdot37)=\sqrt4\cdot√(37)=2√(37)\n\n\n===========================\n\n\sqrt[4]{80}=\sqrt[4]{16\cdot5}=\sqrt[4]{16}\cdot\sqrt[4]5=2\sqrt[4]5

Which statement about the solution to the following system of equations is true?3x - 2y = 4
-6x + 4y = -8

A) There is no solution because the equation represents the same line
B) There is no solution because the equations have the same slope
C) There are infinitely many solutions because the lines have the same slope and different y-intercepts.
D) There are infinitely many solutions because the equations represent the same line

Answers

Let's solve and find out.

3x - 2y = 4
-6x + 4y = -8

To solve by elimination, multiply the top equation by 2 to cancel out y-terms.

2(3x - 2y = 4)
6x - 4y = 8

Now, add the equations together.

     6x - 4y = 8
   -6x + 4y = -8
+___________
     0  -  0  =  0

Since we get that 0 = 0, this system has infinitely many solutions. Only graphs that represent the same line have infinitely many solutions, so...

Answer:
D) There are infinitely many solutions because the equations represent the same line

Length is 380 miles with is 280 miles what is the area

Answers

Area is length x width

So multiply 380 x 280 = 106,400 would be the answer.
area = 380*280=106,400

What is the ratio in simplest form 13:39

Answers

the ratio is 1/3 or 0.33333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333

What is the complete factorization of x2 + 2x − 63? A. (x + 21)(x − 3) B. (x − 9)(x + 7) C. (x + 9)(x − 7) D. (x − 21)(x + 3)

Answers

Answer:

(x + 9)(x - 7)

Step-by-step explanation:

We want to factorize x^2 + 2x - 63

We need to find two numbers such that their product is -63 and they add up to +2. The two numbers are +9 and -7:

x^2 + 9x - 7x - 63\n\n= x(x + 9) -7(x +9)\n\n = (x +9)(x -7)

The complete factorization is (x + 9)(x - 7)

The factored form of the expression x² + 2x - 63 is (x + 9)(x - 7).

What is the factored form of the expression?

Given the expression in the question:

x² + 2x - 63

To determine the complete factorization of the quadratic expression x² + 2x - 63, we aim to break it down into its simplest factors.

This is achieved through factoring, a process of identifying the expressions that, when multiplied, result in the original quadratic expression.

x² + 2x - 63

Now, find a pair of integers whose sum equals 2,

and whose product equals -63.

We use integers 9 and -7.

Next, rewrite the quadratic expression using these factors:

(x + 9)(x - 7)

Therefore, the complete factorization of x² + 2x - 63 is (x + 9)(x - 7).

Option C) (x + 9)(x - 7) is the correct answer.

Learn more about factorization here: brainly.com/question/20293447

#SPJ6

How do i solve this??? added a pic

Answers

x= -4  y=16-5=11

x= -2  y=4-5= -1

x= -1  y=1-5= -4

x= 0  y= -5

x= 1  y= 1-5= -4

x= 2  y=4-5= -1

x=3  y=9-5=4

x=4  y=16-5=11